Controllable field-free switching of perpendicular magnetization through bulk spin-orbit torque in symmetry-broken ferromagnetic films - Xuejie Xie (Nature Portfolio, 2021)
A major challenge of spintronics is achieving magnetic field free electrical control of magnetisation. Here, Xie et al. achieve perpendicular magnetisation switching in a CoPt alloy, breaking inversion symmetry by varying the composition of the alloy in the growth direction.